2021
DOI: 10.3390/cancers13112779
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Cancer Drivers Using DRIVE: A Feature-Based Machine Learning Model for a Pan-Cancer Assessment of Somatic Missense Mutations

Abstract: Sporadic cancer develops from the accrual of somatic mutations. Out of all small-scale somatic aberrations in coding regions, 95% are base substitutions, with 90% being missense mutations. While multiple studies focused on the importance of this mutation type, a machine learning method based on the number of protein–protein interactions (PPIs) has not been fully explored. This study aims to develop an improved computational method for driver identification, validation and evaluation (DRIVE), which is compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…A Schematic diagram showing an overview of DRIVE, a feature-based machine learning platform for pan-cancer assessment of somatic missense mutations, modified from Ref. [ 142 ]. This approach uses a total of 51 features spanning the gene and mutation levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A Schematic diagram showing an overview of DRIVE, a feature-based machine learning platform for pan-cancer assessment of somatic missense mutations, modified from Ref. [ 142 ]. This approach uses a total of 51 features spanning the gene and mutation levels.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Dragomir et al developed and reported a new method (DRIVE) that utilizes machine learning techniques to identify driver and passenger mutations (Fig. 3 A) [ 142 ]. Mutation-level characteristics are based on pathogenicity scores, while gene-level characteristics include the maximum number of protein-protein interactions, biological processes, and types of post-translational modifications.…”
Section: Ai-based Prediction Of Biological Significance For Genetic A...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results acquired with the projected model are manifested in Table II Bi-GRU, SVM, DRIVE [28] and EARN [5], respectively. I-RNN model has recorded the highest accuracy as 95.5%, which is better than the existing models.…”
Section: K Statistical Analysismentioning
confidence: 99%
“…For example, H3 lysine 4 (H3K4me3) and 5 -C-phosphate-G-3 (CpG) methylation alteration are related to transcription elongation, enhancer activity, and repression of tumor suppressors [14]. Genomic features include the maximum number of protein-protein interactions, biological principle types of cells, and post-translational modification (PTM) [15].…”
Section: Introductionmentioning
confidence: 99%